The inﬂuence of coating-carbonization cycles toward P84 co-polyimide/nanocrystalline cellulose - Norazlianie, Sazali; Wan Norharyati, Wan Salleh; Nor Hafiza, Ismail; Ahmad Fauzi, Ismail; Hideyuki, Murakami; Iwamotoe, Yuji (Elsevier, 2019)
Assessment and manufacturing of tubular carbon membrane from P84 co-polyimide (PI) mixtures and Nanocrystalline cellulose (NCC) are described in this study. According to the previous work, a hypothesis was formulated stating that manipulation of carbonization parameters is able to control tubular carbon membrane performance. This study introduces effective dip-coating methods for high performance tubular carbon membrane production. Based on the outcome of this study, the coatingcarbonization cycle (1, 2, 3, and 4 times) has been recognized as major influence on the separation efficiency. Gas separation performance, selectivity, permeability as well as transport mechanism of the carbon membranes were adequately evaluated by pure O2, and N2. The PI/NCC SEM images showed that all the carbon membranes samples comprised of dense structure while the FTIR analysis exposes that existence of functional groups is decreased for all coating-carbonization-cycles samples. The XRD result shows that the membrane carbon structures are amorphous in nature. In this research, application of 2-cycles of coating-carbonization has resulted in carbon membrane with the highest selectivity and O2 permeability which are 9.29±2.54 and 29.92±2.98 GPU, respectively.